2021
DOI: 10.2174/1567201818666210525154345
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic Nanowhiskers: Preparation and Drug Delivery Application

Abstract: : Nanomaterials have applications in almost every field and among them, green nanomaterials have various biological applications. Green nanomaterials are specifically useful for drug and DNA delivery applications. Considering that cellulose is the most abundant and easily available biomolecules, and it has been used for preparing greener cellulose nanomaterials. Cellulosic nanowhiskers are a cost-effective and green alternative to chemical non-viral gene delivery systems. Cellulose nanowhiskers are commonly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…International Journal of Nanomedicine 2023:18 5398 nanomaterials are particularly suitable for drug and DNA delivery, eg, cellulose, a readily available biomolecule, is often used as a green alternative to chemical nonviral gene delivery systems. 208 The goal of reconstructive surgery is to restore form and function, and commonly used methods such as microvascular free flap transfers often result in severe pain, sensory nerve disorders, or concomitant scar formation. On the other hand, tissue engineering techniques based on stem cell research can promote the regeneration of hard and soft tissues and induce the reconstruction of defective areas, promising an alternative to current surgical repair techniques.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…International Journal of Nanomedicine 2023:18 5398 nanomaterials are particularly suitable for drug and DNA delivery, eg, cellulose, a readily available biomolecule, is often used as a green alternative to chemical nonviral gene delivery systems. 208 The goal of reconstructive surgery is to restore form and function, and commonly used methods such as microvascular free flap transfers often result in severe pain, sensory nerve disorders, or concomitant scar formation. On the other hand, tissue engineering techniques based on stem cell research can promote the regeneration of hard and soft tissues and induce the reconstruction of defective areas, promising an alternative to current surgical repair techniques.…”
Section: Dovepressmentioning
confidence: 99%
“…Studies have shown that green nanomaterials are particularly suitable for drug and DNA delivery, eg, cellulose, a readily available biomolecule, is often used as a green alternative to chemical nonviral gene delivery systems. 208 …”
Section: Summary and Prospectsmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop a new mode of drug delivery for the treatment of RA, and the emergence of transdermal drug delivery systems has brought new hope to researchers [6][7][8] . Nanocrystals (NC), also known as nanosuspensions are nanostates (1 ~ 1000 nm) in which the drug is stably dispersed with the help of a small amount of surfactant or in the presence of polymeric materials, and contain close to 100% of the drug [9,10] . Nanocrystalline drugs can increase the solubility of insoluble drugs and improve their bioavailability by reducing the particle size and increasing the speci c surface area of drug particles [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop a new mode of drug delivery for the treatment of RA, and the emergence of transdermal drug delivery systems has brought new hope to researchers [6][7][8] . Nanocrystals (NC), also known as nanosuspensions are nanostates (1 ~ 1000 nm) in which the drug is stably dispersed with the help of a small amount of surfactant or in the presence of polymeric materials, and contain close to 100% of the drug [9,10] . Nanocrystalline drugs can increase the solubility of insoluble drugs and improve their bioavailability by reducing the particle size and increasing the speci c surface area of drug particles [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%